The development of an immobilised-enzyme bioprobe for the detection of phenolic pollutants in water - Russell, Ingrid Margaret (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1999)
The possibility of developing an immobilised-enzyme bioprobe, based on mushroom polyphenol oxidase, for the purely biological detection and quantification of phenolic pollutants in water was investigated. Polyphenol oxidase catalyses the bioconversion of many phenolic compounds into quinone-related coloured products. Thus, in an immobilised form, the enzyme serves as a visible indicator of the presence and concentration of phenolic pollutants in water. The objective of this research was to develop a portable, disposable bioprobe incorporating polyphenol oxidase for this purpose. The intensity of the colour changes produced by the enzyme on reaction with p-cresol, p-chlorophenol and phenol was found to increase proportionally with increasing concentrations of these substrates in solution. Immobilisation of the enzyme on various supports did not appear to significantly affect the catalytic activity of the enzyme. The enzyme was immobilised by adsorption and cross-linking on polyethersulphone, nitrocellulose and nylon membranes with the production of various colour ranges on reaction with the phenolic substrates. The most successful immobilisation of the enzyme, in terms of quantity and distribution of enzyme immobilised and colour production, was obtained with the enzyme immobilised by adsorption on nylon membranes in the presence of 3-methyl-2-benzothiazolinone hydrazone (MBTH). The enzyme, immobilised using this method, produced ranges of maroon colours in phenolic solutions and orange colours in cresylic solutions. The colour intensities produced were found to increase proportionally with increasing substrate concentration after 5 minutes exposure to the substrates. The bioprobe had a broad substrate specificity and was sensitive to substrate concentrations down to 0.05 mg/L. The enzyme activity of the bioprobe was not significantly affected in a pH range from 4 to 10 and in a temperature range from 5-25â °C. The bioprobe activity was not affected by various concentrations of salt and metal ions and the bioprobe was able to detect and semi-quantify phenolic substrates in industrial effluent samples. These features of the bioprobe indicate that the commercialisation of such a bioprobe is feasible and this technology has been patented (Patent No. SA 97/0227).,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Pollutants -- Biodegradation; Pollutants; Chemical reactors; Membrane reactors; Fungi -- Biotechnology